2019
DOI: 10.1108/aeat-06-2018-0175
|View full text |Cite
|
Sign up to set email alerts
|

Flow separation control of NACA-2412 airfoil with bio-inspired nose

Abstract: Purpose The purpose of this paper is to achieve an optimum flow separation control over the airfoil using passive flow control method by introducing bio-inspired nose near the leading edge of the NACA 2412 airfoil. Design/methodology/approach Two distinguished methods have been implemented on the leading edge of the airfoil: forward facing step, which induces multiple accelerations at low angle of attack, and cavity/backward facing step, which creates recirculating region (axial vortices) at high angle of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…The dimensions of this modification can be seen in Figure 2. This dimension was first introduced by Mohamed et al [18]. All dimensions are shown in the form of multiplication of the values of c. The symbol c is the length of the airfoil chord [19].…”
Section: B Modification Of Airfoilsmentioning
confidence: 99%
“…The dimensions of this modification can be seen in Figure 2. This dimension was first introduced by Mohamed et al [18]. All dimensions are shown in the form of multiplication of the values of c. The symbol c is the length of the airfoil chord [19].…”
Section: B Modification Of Airfoilsmentioning
confidence: 99%
“…The bio-inspired nose designs, which are inspired by the cetacean species nose designs, were analyzed for the subsonic speed and found that the Dall’s Porpoise nose showed the better aerodynamic efficiency at all angles of attack with increase in C l (Raj Mohamed et al , 2019). The optimum bio-inspired (porpoise) nose enhances the aerodynamic efficiency for different NACA 4 and 6 series airfoils; hence, it can be made as a simple and fixed LE device which can be installed easily on the existing aircrafts (Raj Mohamed et al , 2021).…”
Section: Introductionmentioning
confidence: 99%